Investigating genotype and sex susceptibility to a systemic infection in APPswe/PS1ΔE9 mouse model of Alzheimer’s disease, at an early stage of amyloid plaque deposition - Agostini, Alessandra (2020)
Systemic bacterial infection can worsen Alzheimer’s disease (AD) progression by compromising the central microglia and astrocytes immune response implicated in the clearance of amyloid-β (Aβ) plaques, one of the AD hallmarks. In the present thesis, I investigated whether systemic infection with lipopolysaccharide (LPS) enhanced glial activation, increased amyloid plaque load and infiltration of peripheral macrophages into the brain and whether tolerance occurred following repeated LPS injections. The incidence of AD is higher in women than in men, thus sex-differences in the immune response were also investigated.